The Evaluation of Cultural Differences on the Identity of the Window Display: The Case Study of the Perception of British and Thai Consumers - Kanokwan Somoon; Chumporn Moorapun (My University, 2017)
Window display is a marketing tool for products presentation and sale promotion as well as product image promotion. There are some researches that tried to describe relationship between consumer behavior and window display design by using marketing concept and psychologically acknowledge but they are not involve to cross culture. However, consumer’s perception depends on their background, experience and cultural factor. Our research attempts to evaluate the cross culture consumer perception on window display identity; case study on the Thai and British. The study based on cross cultural perception, environmental psychology and design elements of shop window display concept. The photograph of shop window display and questionnaire were used for the research tools. Finally, the research found that Thai and British view the design of window display as a whole as well as its light, colour, composition and theme’s concept are the design elements that work as the stimulus to consumers. The consumer’s perception was described by 13 bi-polar words. Factor analysis was used to group and reduce variables. The new variables were pleasant/unpleasant and arousing/not arousing that were used for creates a model that describe the consumer feeling on window display identity.
Keywords: Promotion (chess); Consumer behaviour; Consumer Behavior in Brand Consumption and Identification